Cardiovascular Activities Of Vernonia Amygdalina - Tan, Ming Hooi (2017)
A few reviews on the ethno-medicinal use of Vernonia amygdalina for hypertension have been documented, but the scientific investigations are still very limited. The research was aimed to study the in vitro and in vivo cardiovascular effects of V. amygdalina leaf extracts. The dried leaf samples were successively extracted with petroleum ether (VAPE), chloroform (VACE), methanol (VAME) and water (VAWE). These extracts were examined for vasorelaxant activity in isolated rat thoracic aortic rings, hypotensive activity in anesthetized rats, anti-hypertensive activity, arterial stiffness and biochemical changes in spontaneous hypertensive rats (SHRs).